Determination of the Winner of Project Tender Using Analytical Hierarchy Process - Julian Supardi; Endang Lestari (Generic, 2010)
Determination of the winner project tender is a fairly complex job. This is because the selection of winners is based on various criteria. On the other hand Analytical Hierarchy Process (AHP) is one method frequently used in the development of Decision Makers System. The principle of AHP method is choice of a decision based on consideration of various criteria. Such conditions make the AHP method suitable to be applied in determining the winner of the tender project. In this research, AHP architecture uses seven criteria, and seven alternatives. The seven criteria are price, specification, time, support, warranty, experience, and the browser. Meanwhile, the company that the alternatives to be selected are companies that have passed the prequalification stage. The winner is determined based on the order of greatest priority value.